Barriers to recruiting ethnic minorities to mental health research: a systematic review. Issue 1 (28th January 2014) - Brown, Gillian; Marshall, Max; Bower, Peter; Woodham, Adrine; Waheed, Waquas
Abstract Disparities in the prevalence of mental illness are widely reported for people from ethnic minorities. Unlike the United States, there is no legislation for clinical research in the UK to mandate the inclusion of ethnic minorities and they are underrepresented in European trials compared with those conducted in the United States. This restricts generalization of research findings. This systematic review of the barriers to the recruitment of ethnic minority participants into psychiatric research is based on a comprehensive literature search. Nine included papers explore such barriers based on the authors' and participants' experiences of research. These barriers are mainly categorized as: participant related, practical issues, family/community related, health service related and research process issues. This review provides a compilation of important barriers to recruitment which can facilitate future research. The barriers that were identified are not all unique to participants from ethnic minorities, although the way in which they manifest themselves is often distinct in minority groups. It is important that these barriers are considered when designing research design so that solutions to overcome such obstacles can be incorporated in research protocols from the start and appropriate resources allocated. Copyright © 2014 John Wiley & Sons, Ltd.